Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The impact of digital transformation in general education schools in facing challenges and continuous developments in the world from the point of view of teachers in Makkah Al-Mukarramah regionMr. Maher Abdulrahman Alnemari2. Attitudes of Science Teachers towards Development of Physical Concepts using Virtual laboratories and their ObstaclesMr. Abdullah Sahal Al-Otibi3. Attitudes of Primary Stage Teachers Towards the Use of Active Learning Methods in Teaching  in Sahab Brigade Schools in Amman GovernorateMrs. Weam Waleed Abbas4. Application Requirements for E-management in Yemeni Ministry of Youth and SportsProf. Hussein Salah Juaim, Mr. Kamal Ali Ahmed5. Wisdom-based Thinking and Hexagonal Achievement Goal Approaches of Outstanding  and Superior Students in the Secondary Stage in Makkah CityMrs. Shurog Ahmed Alshehri, Co-Prof. Yasser Abdullah Hefny6. The Psychometric Characteristics of a scale for parental emotional blackmailMrs. Lamia Ibrahim Alshamsan, Prof. Sufyan Ibrahim Alrebdi7. The level of school bullying with middle school stage pupils - A field study at middle schools in Algiers-Dr. Abib Ghania, Dr. Lallouche Saliha
Keywords: Journal of Educational and Psychological Sciences